S-ALLYL-L-CYSTEINE-INDUCED ANTI-INFLAMMATORY AND ANTI-APOPTOTIC EFFECTS IN CHONDROCYTES IS ASSOCIATED WITH SUPPRESSION OF THE MITOCHONDRIAL INFLAMMATION PATHWAY - AHMED, H; FAZAL, N; AHMAD, MR; IJAZ, B; BILAL, AZ; ILYAS, S; MALIK, K; LATIEF, N (Biological and Clinical Sciences Research Journal, 2022)
One major aspects to consider while dealing with osteoarthritis is oxidative stress. This deleterious oxidative stress is responsible for the increased production of Reactive Oxygen Species and triggers several inflammatory pathways, including Mitochondrial Inflammation Pathway (MIP), which leads the cell to apoptosis. Chondrocytes, under oxidative stress, are unable to synthesize cartilage efficiently. S-Allyl-L-Cysteine (SAC) is known to be a potent natural, water-soluble antioxidant derived from garlic whose antioxidant properties have been evaluated in several diseases at the molecular level; other than osteoarthritis. Herein, we investigated the potential of S-Allyl-L-Cysteine (SAC) preconditioning of chondrocytes against oxidative stress-mediated mitochondrial inflammation. SAC priming alleviated oxidative stress-induced injuries by significantly improved cell viability, morphology and activated cell migration. In addition, decreased lactate dehydrogenease, increased superoxide dismutase release and retention of glycosaminoglycans were observed.SAC preconditioning ameliorated the injurious effects of oxidative stress as revealed by significant downregulation in gene expression of hypoxia-induciblefactor 1α (Hif-1α), Xanthine Oxidase (XO), Caspase-9 (Casp-9), Caspase-3(Casp-3), Interleukin 1 beta (IL-1β) and inducible nitric oxide synthase (iNOS). These findings suggest that SAC preconditioning might enhance the antioxidant and anti-inflammatory efficacy of chondrocytes by regulating the MIP pathway and improving cellular responses.